Cardiac antiapoptotic and proproliferative effect of recombinant human erythropoietin in a moderate stage of chronic renal failure in the rat - Teixeira, M. (2012)
Objective: Recombinant human erythropoietin (rhEPO) therapy under circumstances of moderate chronic renal failure (CRF), with yet lower kidney and heart lesion, may have a protective cardiac effect beyond the correction of anemia, whose mechanism deserves better elucidation, namely by clarifying the impact on gene expression profile of markers of apoptosis, inflammation, proliferation, angiogenesis, and lesion/stress in the heart. Materials and Methods: Four groups of rats were studied over a period of 15 weeks (n=7 each): control-without surgery and without drug treatment; rhEPO-treated with 50 IU/kg/week of rhEPO-beta; CRF-submitted to partial nephrectomy (3/4); CRF + rhEPO-CRF with rhEPO treatment after the 3rd week of surgery. The heart was collected in order to evaluate the gene expression, by real-time qPCR, of markers of apoptotic machinery, inflammation/immunology, proliferation/ angiogenesis, and lesion/stress. Results: The main findings obtained were (a) CRF rats have demonstrated overexpression of EPO-R in the heart without changes on EPO expression, together with overexpression of Bax/Bcl2 ratio, PCNA, and IL-2; (b) rhEPO therapy on the heart of the rats with CRF induced by partial 3/4 nephrectomy promoted nonhematopoietic protection, demonstrated by the apoptosis prevention, viewed by the Bax/Bcl2 balance, by the promotion of proliferation, due to PCNA increment, and by the immunomodulatory action, expressed by a trend to prevent the IL-2 increment. Conclusion: In this model of moderate CRF, rhEPO treatment showed important cardiac nonhematopoietic effects, expressed mainly by the antiapoptotic and the proproliferative action, suggesting that early rhEPO therapy in moderate stages of CRF might have further therapeutic benefits.